Shields of the shore: mangrove ecosystem shifts and climate vulnerability in Mozambique - Foggia, Camilla; Attorre, Fabio; Bourgeois, Carine; Candeago, Elisabetta; Ramoni-Perazzi, Paolo; Malatesta, Luca (Frontiers in Forests and Global Change, 2025)
IntroductionDue to its vulnerability to climate-driven floods and storms, Mozambique faces significant challenges in coastal planning due to limited reliable data. In this context, studying mangrove cover and dynamics could provide valuable insights to enhance coastal area management.MethodsThis study introduces an innovative framework that assesses mangrove extent and coastal vulnerability by integrating the Mangrove Vegetation Index (MVI) with the InVEST Coastal Vulnerability model to accurately identify areas of highest priority for intervention. Using MVI applied to Landsat-8 (30 m) and Sentinel-2 (2023, resampled from 10 m to 30 m) imagery, we mapped mangrove cover for 2013 and 2023, refining accuracy by excluding pixels beyond 1.2 km inland and above 10 m elevation. A cloud-based workflow leveraging Google Earth Engine and QGIS enabled scalable, efficient analysis.ResultsThe mangrove area declined from 2,116 km2 in 2013 to 1,739 km2 in 2023—a 18% loss, equivalent to 1.8% annually. The results of the Coastal Vulnerability Model, applied to the entire coast of Mozambique, produced an Exposure Index (EI) for flooding and erosion events. Each point along the coast was classified with values from 1 to 5 at a distance of 100 m from each other: the highest values indicating greater exposure. It emerged that 16.2% of the 11,768.11 km of coastline were classified with an EI as ‘Very Low’, 42% as ‘Low’, 32% as ‘Intermediate’, 9.4% as ‘High’ and 0.1% as ‘Very High’. Considering the points classified with a ‘High’ and ‘Very High’ EI, approximately 1,117.97 km of coastline is highly vulnerable and in need of intervention. Analysis of the impact of Cyclone Idai (2018–2019) on the Púnguè and Buzi River delta revealed a 69% reduction in mangrove cover, from 76 km2 to 23 km2.DiscussionThese findings underscore the urgent need for targeted interventions, prioritizing Sofala and Zambezia for mangrove restoration and nature-based solutions to bolster coastal resilience. This scalable approach advances global mangrove monitoring and supports data-driven coastal management in climate-vulnerable regions.